.12y-.72+.06y=.08y-.7

Simple and best practice solution for .12y-.72+.06y=.08y-.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .12y-.72+.06y=.08y-.7 equation:


Simplifying
0.12y + -0.72 + 0.06y = 0.08y + -0.7

Reorder the terms:
-0.72 + 0.12y + 0.06y = 0.08y + -0.7

Combine like terms: 0.12y + 0.06y = 0.18y
-0.72 + 0.18y = 0.08y + -0.7

Reorder the terms:
-0.72 + 0.18y = -0.7 + 0.08y

Solving
-0.72 + 0.18y = -0.7 + 0.08y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.08y' to each side of the equation.
-0.72 + 0.18y + -0.08y = -0.7 + 0.08y + -0.08y

Combine like terms: 0.18y + -0.08y = 0.1y
-0.72 + 0.1y = -0.7 + 0.08y + -0.08y

Combine like terms: 0.08y + -0.08y = 0.00
-0.72 + 0.1y = -0.7 + 0.00
-0.72 + 0.1y = -0.7

Add '0.72' to each side of the equation.
-0.72 + 0.72 + 0.1y = -0.7 + 0.72

Combine like terms: -0.72 + 0.72 = 0.00
0.00 + 0.1y = -0.7 + 0.72
0.1y = -0.7 + 0.72

Combine like terms: -0.7 + 0.72 = 0.02
0.1y = 0.02

Divide each side by '0.1'.
y = 0.2

Simplifying
y = 0.2

See similar equations:

| 4*p*4*p= | | -57=27-6x | | -4(x-1)+2=4+6(-x+3) | | (-4x^3y)(5x^2)(-2xy^5)= | | 36h+20=24h+15 | | 25x-7=5(5x+9) | | 8+5x=x+28 | | Y=B^2-6b+8 | | 22-33w-5w=0 | | 27x-13=0 | | 6x+18-3x=24 | | x(a-b)+2=c(x+3)-d | | 5n-10= | | 0.625xa=1 | | -18+4x=-2 | | (3z^5)(4z^5)= | | 5+5=5(x+7) | | 51=3+12x | | (3x^2+2x+1)-(x^2-3x+4)= | | -20+2k=-4k+k | | (c^9)(c^8)(c)= | | 2p-5=-12 | | 7S(r-3)= | | 1+3x=5(15-x) | | .4x+2.4=4.25 | | 9x^16=0 | | 4x^2-8x-62=0 | | 3x+x+1=9x-5x+2 | | .4x+2.4=4.24 | | 3(8c-4)=21+5c | | 2p+5=-12 | | -2x=-10y+3zx+1 |

Equations solver categories